Menjelajahi Bahasa Inggris Melalui Joyfull Learning: Studi Kasus English Club MIN 3 Pacitan - Puspitasari, Indah; Prastya, Azi’; Aulina, Bella (Scholarly Journal of Elementary School, 2025)
This study aims to determine how the implementation of the Joyful Learning model is in class 2C MIN 3 Pacitan. This research method is qualitative with a case study approach. The research results showed that the implementation of Joyful Learning in class 2C MIN 3 Pacitan went well. Students looked enthusiastic and active in participating in learning activities. The various interactive learning methods used in Joyful Learning help students understand the subject matter, such as the Look and Say game with flashcards, Cut and Stick, Guess the Word with Prizes game, interactive lectures, and dialogues. Learning activities in Joyful Learning include the Visiting a Friend's Table game, the Ball Throwing game, and other relevant activities. The implementation of Joyful Learning in class 2C MIN 3 Pacitan showed positive results. This learning model can create a pleasant classroom atmosphere and motivate students' involvement. The various interactive learning methods are the success key to implementing this learning model.